Highly Boosted Reaction Kinetics in Carbon Dioxide Electroreduction by Surface-Introduced Electronegative Dopants - Zheng, Wanzhen; Wang, Yu; Shuai, Ling; Wang, Xinyue; He, Feng; Lei, Chaojun; Li, Zhongjian; Yang, Bin; Lei, Lecheng; Yuan, Chris; Qiu, Ming; Hou, Yang; et al. (Advanced Functional Materials, 2021)
Effectively improving the selectivity while reducing the overpotential over the electroreduction of CO2 (CO2ER) has been challenging. Herein, electronegative N atoms and coordinatively unsaturated Ni-N3 moieties co-anchored carbon nanofiber (Ni-N3-NCNFs) catalyst via an integrated electrospinning and carbonization strategy are reported. The catalyst exhibits a maximum CO Faradaic efficiency (F.E.) of 96.6%, an onset potential of −0.3 V, and a low Tafel slope of 71 mV dec−1 along with high stability over 100 h. Aberration corrected scanning transmission electron microscopy, X-ray absorption spectroscopy, and X-ray photoelectron spectroscopy identify the atomically dispersed Ni-N3 sites with Ni atom bonded by three pyridinic N atoms. The existence of abundant electronegative N dopants adjoin the Ni-N3 centers in Ni-N3-NCNFs. Theoretical calculations reveal that both, the undercoordinated Ni-N3 centers and their first neighboring C atoms modified by extra N dopants, display the positive effect on boosting CO2 adsorption and water dissociation processes, thus accelerating the CO2ER kinetics process. Furthermore, a designed Zn-CO2 battery with the cathode of Ni-N3-NCNFs delivers a maximum power density of 1.05 mW cm−2 and CO F.E. of 96% during the discharge process, thus providing a promising approach to electric energy output and chemical conversion.
CRIS-Team Scopus Importer:2023-03-20
Keywords: CO; reaction kinetics; simultaneous effects; unsaturated coordination; Zn -CO